Longitudinal atrophy in early Braak regions in preclinical Alzheimer's disease. Issue 16 (26th August 2020) - Xie, Long; Wisse, Laura E. M.; Das, Sandhitsu R.; Vergnet, Nicolas; Dong, Mengjin; Ittyerah, Ranjit; de Flores, Robin; Yushkevich, Paul A.; Wolk, David A.; ,
Abstract: A major focus of Alzheimer's disease (AD) research has been finding sensitive outcome measures to disease progression in preclinical AD, as intervention studies begin to target this population. We hypothesize that tailored measures of longitudinal change of the medial temporal lobe (MTL) subregions (the sites of earliest cortical tangle pathology) are more sensitive to disease progression in preclinical AD compared to standard cognitive and plasma NfL measures. Longitudinal T1‐weighted MRI of 337 participants were included, divided into amyloid‐β negative (Aβ−) controls, cerebral spinal fluid p‐tau positive (T+) and negative (T−) preclinical AD (Aβ+ controls), and early prodromal AD. Anterior/posterior hippocampus, entorhinal cortex, Brodmann areas (BA) 35 and 36, and parahippocampal cortex were segmented in baseline MRI using a novel pipeline. Unbiased change rates of subregions were estimated using MRI scans within a 2‐year‐follow‐up period. Experimental results showed that longitudinal atrophy rates of all MTL subregions were significantly higher for T+ preclinical AD and early prodromal AD than controls, but not for T− preclinical AD. Posterior hippocampus and BA35 demonstrated the largest group differences among hippocampus and MTL cortex respectively. None of the cross‐sectional MTL measures, longitudinal cognitive measures (PACC, ADAS‐Cog) and cross‐sectional or longitudinal plasma NfL reached significance in preclinical AD. In conclusion, longitudinal atrophy measurements reflect active neurodegeneration and thus are more directly linked to active disease progression than cross‐sectional measurements. Moreover, accelerated atrophy in preclinical AD seems to occur only in the presence of concomitant tau pathology. The proposed longitudinal measurements may serve as efficient outcome measures in clinical trials. Abstract : We investigated the utility of tailored measures of longitudinal change of the medial temporal lobe (MTL) subregions quantified from longitudinal structural MRI in tracking disease progression in preclinical Alzheimer's disease. Experiment results showed that our longitudinal measurements are more sensitive to disease progression in preclinical AD compared to longitudinal cognitive (PACC, ADAS‐Cog) and plasma NfL measures. Also, accelerated atrophy in preclinical AD seems to occur only in the presence of concomitant tau pathology. The proposed longitudinal measurements may serve as efficient outcome measures in clinical trials.